Impact of the Omicron Strain on Febrile Convulsions Requiring Hospitalization in Children: A Single-Center Observational Study - Masayuki Nagasawa; Teruyoshi Shimoyama; Sayuri Hashimoto; Ryuichi Nakagawa; Haruna Yokoyama; Mari Okada; Tomohiro Udagawa; Akihiro Oshiba (MDPI AG, 2024)
Background. The emergence of the Omicron strain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at the end of December 2021 has drastically increased the number of infected children in Japan, along with the number of children with febrile convulsions, but its clinical impact is unclear. Materials and Methods. We compared the frequency of SARS-CoV-2 infection in children hospitalized with febrile convulsions with the frequency of SARS-CoV-2 infection in children with fever and respiratory symptoms without convulsions. Results. In 2021 and 2022, 49 and 58 children required emergency hospitalization for febrile convulsions (FC group) with status epilepticus or cluster spasms, in which 24 and 38 children underwent a Filmarray® respiratory panel test (FA test), respectively, and others received a quantitative antigen test for SARS-CoV-2. In 2022, only six patients tested positive for SARS-CoV-2 (10.3%, 6/58). As a reference group, 655 children aged <10 years who underwent the FA test for fever and respiratory symptoms during the same period were investigated, and 4 (1.8%, 4/223) and 42 (9.7%, 42/432) tested positive for SARS-CoV-2 in 2021 and 2022, respectively. Rhinovirus/enterovirus (RV/EV) was the most frequently detected virus (40.3%, 264/655), followed by respiratory syncytial virus (RSV) (18.9%, 124/655) and parainfluenza virus 3 (PIV3) (7.8%, 51/655). There was no significant difference in the trend of detected viruses between the two groups. Conclusions. The frequency and severity of febrile convulsions requiring hospitalization associated with SARS-CoV-2 infection of the Omicron strain may be similar to that of other respiratory viruses in children.